Question

(x+1)y'=y-1 2) dx+(x/y+(e)?)dy=0 3)ty'+2y=sint 4) y"-4y=-3x²e3x 5) y"-y-2y=1/sinx 6)2x2y"+xy'-2y=0 ea)y=x' b) x=0 2dx/dt-2dy/dt-3x=t; 2

(x+1)y'=y-1 2) dx+(x/y+(e)?)dy=0 3)ty'+2y=sint 4) y"-4y=-3x²e3x 5) y"-y-2y=1/sinx 6)2x2y"+xy'-2y=0 ea)y=x' b) x=0 2dx/dt-2dy/dt-3x=t; 2

Homework Answers

Know the answer?
Your Answer:

Post as a guest

Your Name:

What's your source?

Earn Coins

Coins can be redeemed for fabulous gifts.

Not the answer you're looking for?
Ask your own homework help question
Similar Questions
dx dt = y − 1 dy dt = −3x + 2y x(0) = 0, y(0)...
dx dt = y − 1 dy dt = −3x + 2y x(0) = 0, y(0) = 0
find dy/dx a. (x+y)^4 =4y-9x b. y= (x +6)^2x c. y= cos^-1 (3x^2 -5x +1 )
find dy/dx a. (x+y)^4 =4y-9x b. y= (x +6)^2x c. y= cos^-1 (3x^2 -5x +1 )
Solve the following: (3x^2 - y^2)dx + (xy - x^3y^-1)dy = 0
Solve the following: (3x^2 - y^2)dx + (xy - x^3y^-1)dy = 0
solve for x(t) and y(t): x'=-3x+2y; y'=-3x+4y x(0)=0,y(0)=2
solve for x(t) and y(t): x'=-3x+2y; y'=-3x+4y x(0)=0,y(0)=2
Use the Laplace transform to solve the given system of differential equations. dx/dt=x-2y dy/dt=5x-y x(0) =...
Use the Laplace transform to solve the given system of differential equations. dx/dt=x-2y dy/dt=5x-y x(0) = -1, y(0) = 6
solve the given initial value problem. y(cos2t)e^ty - 2(sin2t)e^ty + 2t + (t(cos2t)e^ty - 3) dy/dt...
solve the given initial value problem. y(cos2t)e^ty - 2(sin2t)e^ty + 2t + (t(cos2t)e^ty - 3) dy/dt = 0, y(0)=0
Solve the initial value problems. 1) x (dy/dx)+ 2y = −sinx/x , y(π) = 0. 2)...
Solve the initial value problems. 1) x (dy/dx)+ 2y = −sinx/x , y(π) = 0. 2) 3y”−y=0 , y(0)=0,y’(0)=1.Use the power series method for this one . And then solve it using the characteristic method Note that 3y” refers to it being second order differential and y’ first
Initial value problem : Differential equations: dx/dt = x + 2y dy/dt = 2x + y...
Initial value problem : Differential equations: dx/dt = x + 2y dy/dt = 2x + y Initial conditions: x(0) = 0 y(0) = 2 a) Find the solution to this initial value problem (yes, I know, the text says that the solutions are x(t)= e^3t - e^-t and y(x) = e^3t + e^-t and but I want you to derive these solutions yourself using one of the methods we studied in chapter 4) Work this part out on paper to...
3. Consider the equation (3x^2y + y^2)dx + (x^3 + 2xy + 5)dy = 0. (a)...
3. Consider the equation (3x^2y + y^2)dx + (x^3 + 2xy + 5)dy = 0. (a) Verify this is an exact equation (b) Solve the equation
dy/dt=x , dx/dt=6x-8y, x=1 and y=-1 when t=0
dy/dt=x , dx/dt=6x-8y, x=1 and y=-1 when t=0